The Effect of Holistic Comprehensive Health Service Approach Through Family Functions on Optimizing the Nutrition Status of Junior High School Students - Febri Endra Budi Setyawan; Carla Edhina Widiadi (Universitas Muhammadiyah Malang, 2020)
Background : Nutritional status problems have many causes, including genetic, body metabolic conditions, behavior, environment, culture, and socioeconomic factors. One environmental factor that receives relatively limited attention is that children are exposed to undue stress, especially family stress. One of the factors influencing a child's nutritional status is his family. Family functions that run well can optimize the process of growth and development of children which can be described by the nutritional status. Optimization of nutritional status in children can not only be done from a clinical approach alone but needs holistic comprehensive management.Objective : The purpose of the study was to analyze the effect of a holistic comprehensive health service approach through family functions on optimizing the nutritional status of junior high school students.Method : This study was an observational analytic study with a cross sectional approach with the subjects of Malang City's